The little data book on private sector development 2008 (World Bank, 2008)
The Little Data Book on Private Sector Development 2008 is one of a series of pocket-sized books intended to provide a quick reference to development data on different topics. The Little Data Book on Private Sector Development 2008 provides data for more than 20 key indicators on business environment and private sector development in a single page for each of the World Bank member countries and other economies with populations of more than 30,000. These more than 200 country pages are supplemented by aggregate data for regional and income groupings.